Public Service Quality Policies in West Seram District - Hendry Selanno; Rahawarin, Mohamad Arsad; Jeanly Waisapy (Dinasti Publisher, 2024)
This study aims to evaluate public service quality policies in West Seram District. This research was conducted for one year using a qualitative approach and a descriptive research design. The unit of analysis in this study is the implementation of public service quality policies in West Seram District on the aspects of resources, communication, disposition, and bureaucratic structure. Data is obtained through informants representing all parties related to the policy implementation. The results of the study show that: (1) Aspects of Resources; (a) human resources are sufficient in terms of quantity, but it is still necessary to improve discipline in terms of timing and appropriateness, and consistency in completing service tasks to ensure employee performance accountability, (b) the resources for facilities and infrastructure are inadequate and unable to support the improvement of service quality. (2) the communication aspect is going well, as shown by the behavior of employees who are friendly, polite, and courteous to people who need services but are still constrained by low public awareness to follow and comply with the required provisions. (3) the disposition aspect has been well implemented, as indicated by the high awareness of all elements of the leadership and employees of the West Seram District Office regarding their duties, responsibilities, and authorities as community servants. However, limited services can still be provided by the Subdistrict head’s office and the little delegation of authority form the Regent, resulting in minimal space for service. (4) the Bureaucratic Structure Aspect is running well following the main tasks and functions, which is shown by the enactment of rules related to the provision of service activities following work procedures in each field.